2016
DOI: 10.1177/0885066616686052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Etomidate on Pneumonia Development in Critically Ill, Nontrauma Patients

Abstract: Etomidate use was not associated with a difference in HAP development in critically ill, nontrauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This finding is consistent with previous reports that single-dose etomidate is associated with a higher incidence of hospital-acquired pneumonia after cardiac surgery and that etomidate is an independent risk factor for hospital-acquired pneumonia in patients with trauma . However, another retrospective study in patients with critical illness reported no association between single-dose etomidate and pneumonia . Nonetheless, the collective evidence supports cautious use of etomidate infusion in patients at risk for pulmonary complications.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with previous reports that single-dose etomidate is associated with a higher incidence of hospital-acquired pneumonia after cardiac surgery and that etomidate is an independent risk factor for hospital-acquired pneumonia in patients with trauma . However, another retrospective study in patients with critical illness reported no association between single-dose etomidate and pneumonia . Nonetheless, the collective evidence supports cautious use of etomidate infusion in patients at risk for pulmonary complications.…”
Section: Discussionmentioning
confidence: 92%
“…9 However, another retrospective study in patients with critical illness reported no association between single-dose etomidate and pneumonia. 8 Nonetheless, the collective evidence supports cautious use of etomidate infusion in patients at risk for pulmonary complications. Given the relevance of pulmonary complications for mortality in older patients after major surgery, this issue requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations